2005
DOI: 10.1097/01.phm.0000153323.28396.de
|View full text |Cite
|
Sign up to set email alerts
|

Physicians with Disabilities and the Physician Workforce: A Need to Reassess Our Policies

Abstract: People with disabilities make up about 20% of the population, yet only a tiny fraction of matriculants to medical school have disabilities. Attempts to define core technical standards and competencies have not kept pace with technological changes, diverse specialization, and changing practice options. This has resulted in the inappropriate exclusion of some people with disabilities. Medical schools determine how any qualified applicant, regardless of physical or cognitive ability, can be effectively accommodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…much additional time, talents, and training were needed to train MSPD. 26 Dr. DeLisa countered that MSPD were no more likely than other medical students to engage in reckless and dangerous acts. 26 Previous study had shown that MSPD performed academically at the same level as their nondisabled peers.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…much additional time, talents, and training were needed to train MSPD. 26 Dr. DeLisa countered that MSPD were no more likely than other medical students to engage in reckless and dangerous acts. 26 Previous study had shown that MSPD performed academically at the same level as their nondisabled peers.…”
Section: Discussionmentioning
confidence: 94%
“…26 Dr. DeLisa countered that MSPD were no more likely than other medical students to engage in reckless and dangerous acts. 26 Previous study had shown that MSPD performed academically at the same level as their nondisabled peers. 16 There was no reason to suggest that academic standards for MSPD had for some reason fallen during the course of the past 25 yrs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the issues of disability and health are closely wedded to those of individual entitlement and access, they also have resonance for patient care. It is to be noted that health care professionals with disabilities feel they can achieve improved communication with patients, and a better understanding of their needs, as a result of their own experiences of living with disability 9,22,23 . A patient may well value the fact that a doctor who is providing care has overcome his or her own difficulties related to disability or ill health and, therefore, may well be better able to empathise with and support the patient.…”
Section: Discussionmentioning
confidence: 99%
“…disclosed a disability, at least a proportion of whom will have had a disability at the time of medical school (DeLisa and Thomas 2005). It may be that not all medical students disclose disability, possibly due to fear of discrimination, or not regarding themselves as disabled, or being apprehensive of the potential outcome of disclosure (Social Care Workforce Research Unit 2007).…”
Section: Practice Pointsmentioning
confidence: 99%